Crystal of thiophene derivative and method for producing same
The development of thiophene derivative crystals with specific X-ray diffraction patterns addresses the limitations of existing urate-lowering drugs by providing a stable and non-hygroscopic medicine for treating gout and hyperuricemia, offering effective xanthine oxidase inhibition and uric acid uptake inhibition.
Patent Information
- Application Number
- JP2023566003
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-18
- Filing Date
- 2022-04-21
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-04-21
AI Technical Summary
Current urate-lowering drugs for hyperuricemia and gout, such as xanthine oxidase inhibitors like allopurinol and febuxostat, have limitations in efficacy and safety, particularly for patients with high doses, and there is a need for safer and more effective treatments.
Development of crystals of a thiophene derivative with specific powder X-ray diffraction patterns, characterized by distinct 2θ angles, which exhibit stable physical properties and are not hygroscopic, potentially serving as a medicine for treating gout and hyperuricemia.
The thiophene derivative crystals demonstrate effective xanthine oxidase inhibition and uric acid uptake inhibition, showing good stability and non-hygroscopicity, indicating potential as a safe and effective treatment for hyperuricemia and gout.
Smart Images

Figure 0007602065000033 
Figure 0007602065000034 
Figure 0007602065000035
Abstract
Description
[Technical field]
[0001] The present invention relates to a crystal of a thiophene derivative and a method for producing the same, and more particularly to a crystal of a compound represented by formula (I) and a method for producing the same. [Background technology]
[0002] This invention claims priority to the following: CN202110472705.3, filing date: April 29, 2021; CN202111112439.X, Application date: September 18, 2021.
[0003] Gouty arthritis is a common and complicated type of arthritis. When the concentration of uric acid in the human blood exceeds 7 mg / dL, uric acid is deposited in the form of monosodium salt in the joints, cartilage, and kidneys, which overactivates the body's immune system and causes painful inflammation. Common sites of attack are the big toe joint, ankle joint, knee joint, etc. Hyperuricemia is the pathological basis of gouty arthritis. Hyperuricemia refers to a condition in which the synthesis of uric acid in the human body is increased or excreted decreased due to abnormal metabolism of purine substances in the human body, resulting in abnormally high uric acid levels in the blood. Internationally, the diagnosis of HUA is defined as follows: Under normal purine diet, the blood uric acid level in two fasting days on different days is: >400 μmol / L (6.8 mg / dL) for men, and >360 μmol / L (6 mg / dL) for women. It is divided into three types: uric acid excretion type, uric acid overproduction type, and mixed type. Clinical studies have shown that 90% of primary hyperuricemia cases are due to poor urate excretion.
[0004] Hyperuricemia is closely related to gout and is an independent risk factor for metabolic diseases (diabetes, metabolic syndrome (MS), hyperlipidemia, etc.), chronic kidney disease, cardiovascular disease, and stroke. Therefore, lowering the uric acid level in the human body can not only be used to treat and prevent hyperuricemia and gout, but also reduce the risk of other complications associated with hyperuricemia.
[0005] There are two sources of purines in the human body: endogenous purines originate from self-synthesis or nucleic acid degradation (about 600 mg / d), and exogenous purines originate from purine dietary intake (about 100 mg / d). Under normal conditions, the uric acid pool in the body is 1200 mg, and about 700 mg of uric acid is produced daily, of which 2 / 3 is excreted by the kidney, 1 / 3 by the intestine, and a small amount is excreted by the sweat gland. Therefore, uric acid lowering drugs currently commonly used in clinical practice include xanthine oxidase inhibitors (such as allopurinol and febuxostat) that inhibit the production of uric acid and Urat1 inhibitors (such as benzbromarone and lesinurad) that excrete uric acid.
[0006] Xanthine oxidase is a low-specificity enzyme that not only catalyzes hypoxanthine to produce xanthine, which then produces uric acid, but also directly catalyzes xanthine to produce uric acid. Xanthine oxidase inhibitors are the first-line treatment for hyperuricemia, and currently available drugs are mainly allopurinol and febuxostat. However, such drugs cannot meet the clinical needs of all patients and also have significant side effects. Allopurinol is the only uric acid lowering treatment available worldwide, but it can cause serious skin adverse events. Allopurinol-related severe hypersensitivity reactions are closely related to human leukocyte antigen (HLA)-B*5801, and the proportion of HLA-B*5801-positive Chinese (6%-8%) is higher than that of Caucasians (~2%), which increases the risk of hypersensitivity reactions. Although febuxostat is more effective at lowering uric acid than allopurinol, at doses as high as 80 mg / day, 40%-52% of patients will not achieve the expected uric acid lowering goal and may increase acute gout attacks. There is an unmet clinical need in the market for safe and effective uric acid lowering drugs. Summary of the Invention
[0007] The present invention provides a type A crystal of the compound of formula (I), which is characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 12.35±0.20°, 15.05±0.20°, 18.19±0.20°, 20.10±0.20°, 23.05±0.20°, 25.05±0.20°, 25.87±0.20°, and 27.16±0.20°. [ka]
[0008] In some embodiments of the present invention, the powder X-ray diffraction pattern of the A-type crystal has characteristic diffraction peaks at the following 2θ angles: 10.89±0.20°, 12.35±0.20°, 13.42±0.20°, 15.05±0.20°, 18.19±0.20°, 20.10±0.20°, 21.82±0.20°, 23.05±0.20°, 25.05±0.20°, 25.87±0.20°, 27.16±0.20°, and 30.28±0.20°.
[0009] In some embodiments of the present invention, the powder X-ray diffraction pattern of the A-type crystal has characteristic diffraction peaks at the following 2θ angles: 6.72°, 8.94°, 10.89°, 12.35°, 13.42°, 15.05°, 17.26°, 18.19°, 18.70°, 20.10°, 21.82°, 23.05°, 24.28°, 25.05°, 25.87°, 27.16°, 29.41°, 30.28°, 30.89°, 33.58°, 36.29°, 37.29°, and 38.99°.
[0010] In some embodiments of the present invention, the XRPD pattern of the Form A crystals is essentially as shown in FIG. In some embodiments of the present invention, the XRPD pattern analysis data of the A-type crystal is as shown in Table 1. [Table 1]
[0011] In some embodiments of the present invention, the thermogravimetric analysis curve of the A-type crystals shows a weight loss of 1.96% at 200°C±3°C. In some embodiments of the present invention, the TGA pattern of the Form A crystals is as shown in FIG.
[0012] In some embodiments of the present invention, the differential scanning calorimetry curve of the A-type crystals has an onset of one endothermic peak at 244.3.0°C ± 2°C. In some embodiments of the present invention, the DSC pattern of the A-type crystals is as shown in FIG.
[0013] The present invention provides a B-type crystal of the compound of formula (I), which is characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 23.93±0.20°, 24.73±0.20°, and 26.58±0.20°. [ka]
[0014] In some embodiments of the present invention, the powder X-ray diffraction pattern of the B-type crystals has characteristic diffraction peaks at the following 2θ angles: 13.02±0.20°, 14.68±0.20°, 16.44±0.20°, 19.50±0.20°, 22.69±0.20°, 23.93±0.20°, 24.73±0.20°, and 26.58±0.20°.
[0015] In some embodiments of the present invention, the powder X-ray diffraction pattern of the B-type crystals has characteristic diffraction peaks at the following 2θ angles: 13.02±0.20°, 14.68±0.20°, 16.44±0.20°, 19.50±0.20°, 22.69±0.20°, 23.93±0.20°, 24.73±0.20°, 25.87±0.20°, 26.58±0.20°, 28.98±0.20°, 29.34±0.20°, and 31.86±0.20°.
[0016] In some embodiments of the present invention, the powder X-ray diffraction pattern of the B-type crystals is obtained by the following 2θ angles: 5.37°, 11.72°, 13.02°, 14.68°, 15.44°, 16.05°, 16.44°, 16.94°, 18.68°, 19.50°, 20.69°, 21.13°, 21.32°, 21.70°, 22.41°, 22.69°, 23.46°, 24.02°, 25.02°, 26.02°, 27.02°, 28.02°, 29.02°, 30.02°, 31.02°, 32.02°, 33.02°, 34.02°, 35.02°, 36.02°, 37.02°, 38.02°, 39.02°, 40.02°, 41.02°, 42.02°, 43.02°, 44.02°, 45.02°, 46.02°, 47.02°, 48.02°, 49.02°, 50.02°, 51.02°, 52.02°, 53.02°, 54.02°, 55.02°, 56.02°, 57.02°, 58.02°, 59.02°, 60.02°, 61.02°, 62.02°, 63.02°, 64.02°, 65.02°, 66.02°, It has characteristic diffraction peaks at 3.93°, 24.73°, 25.87°, 26.58°, 27.78°, 28.98°, 29.34°, 29.66°, 30.07°, 31.26°, 31.38°, 31.86°, 32.73°, 33.71°, 34.02°, 34.68°, 35.41°, 36.64°, 37.30°, 37.86°, and 38.30°.
[0017] In some embodiments of the present invention, the XRPD pattern of the B-type crystals is essentially as shown in FIG. In some embodiments of the present invention, the XRPD pattern analysis data of the B-type crystal is as shown in Table 2.
[0018] [Table 2]
[0019] The present invention provides a crystal of the compound of formula (I), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 13.28±0.30°, 15.34±0.30°, and 25.14±0.30°. [ka]
[0020] In some embodiments of the present invention, the powder X-ray diffraction pattern of the crystals has characteristic diffraction peaks at the following 2θ angles: 9.11±0.30°, 13.28±0.30°, 15.34±0.30°, 18.16±0.30°, 22.06±0.30°, 25.14±0.30°, 26.75±0.30°, and 27.25±0.30°.
[0021] In some embodiments of the present invention, the powder X-ray diffraction pattern of the crystals has characteristic diffraction peaks at the following 2θ angles: 9.11±0.30°, 11.21±0.30°, 13.28±0.30°, 15.34±0.30°, 18.16±0.30°, 22.06±0.30°, 23.15±0.30°, 25.14±0.30°, 25.97±0.30°, 26.75±0.30°, 27.25±0.30°, and 30.82±0.30°.
[0022] The present invention provides a crystal of the compound of formula (I), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 13.20±0.20°, 15.26±0.20°, and 25.07±0.20°. [ka]
[0023] In some embodiments of the present invention, the powder X-ray diffraction pattern of the crystals has characteristic diffraction peaks at the following 2θ angles: 13.20±0.20°, 15.26±0.20°, 18.08±0.20°, 21.99±0.20°, 25.07±0.20°, 26.66±0.20°, 28.38±0.20°, and 30.70±0.20°.
[0024] In some embodiments of the present invention, the powder X-ray diffraction pattern of the crystals has characteristic diffraction peaks at the following 2θ angles: 9.03±0.20°, 11.13±0.20°, 13.20±0.20°, 15.26±0.20°, 18.08±0.20°, 21.99±0.20°, 25.07±0.20°, 26.66±0.20°, 28.38±0.20°, 29.41±0.20°, 30.70±0.20°, and 38.53±0.20°.
[0025] The present invention provides a C-type crystal of the compound of formula (I), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 13.20±0.20°, 18.08±0.20°, and 25.07±0.20°. [ka]
[0026] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 13.20±0.20°, 15.26±0.20°, 18.08±0.20°, 21.99±0.20°, 25.07±0.20°, 26.66±0.20°, 28.38±0.20°, and 30.70±0.20°.
[0027] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 13.20±0.20°, 15.26±0.20°, 18.08±0.20°, 21.99±0.20°, 25.07±0.20°, 25.38±0.20°, 26.66±0.20°, and 30.70±0.20°.
[0028] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.03±0.20°, 11.13±0.20°, 13.20±0.20°, 15.26±0.20°, 18.08±0.20°, 21.99±0.20°, 25.07±0.20°, 26.66±0.20°, 28.38±0.20°, 29.41±0.20°, 30.70±0.20°, and 38.53±0.20°.
[0029] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.03±0.20°, 13.20±0.20°, 15.26±0.20°, 18.08±0.20°, 21.99±0.20°, 25.07±0.20°, 25.38±0.20°, 26.66±0.20°, 28.38±0.20°, 29.41±0.20°, 30.70±0.20°, and 38.53±0.20°.
[0030] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.03±0.20°, 11.13±0.20°, 13.20±0.20°, 15.26±0.20°, 18.08±0.20°, 21.99±0.20°, 24.09±0.20°, 25.07±0.20°, 25.38±0.20°, 26.66±0.20°, 27.17±0.20°, 28.38±0.20°, 29.41±0.20°, 30.70±0.20°, 31.02±0.20°, and 38.53±0.20°.
[0031] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 13.20±0.20°, 25.07±0.20°, and further has characteristic diffraction peaks at 18.08±0.20°, and / or 9.03±0.20°, and / or 11.13±0.20°, and / or 15.26±0.20°, and / or 18.92±0.20°, and / or 21.99±0.20°, and / or 24.09±0.20°, and / or 25.38±0.20°. 0.20°, and / or 26.66±0.20°, and / or 27.17±0.20°, and / or 28.38±0.20°, and / or 29.41±0.20°, and / or 30.70±0.20°, and / or 31.02±0.20°, and / or 33.67±0.20°, and / or 35.40±0.20°, and / or 36.35±0.20°, and / or 37.26±0.20°, and / or 38.53±0.20°.
[0032] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.03°, 11.13°, 13.20°, 15.26°, 18.08°, 18.92°, 21.99°, 24.09°, 25.07°, 25.38°, 26.66°, 27.17°, 28.38°, 29.41°, 30.70°, 31.02°, 33.67°, 35.40°, 36.35°, 37.26°, and 38.53°.
[0033] In some embodiments of the present invention, the powder X-ray diffraction pattern of the C-type crystals has characteristic diffraction peaks at the following 2θ angles: 5.66°, 9.03°, 11.13°, 13.20°, 13.70°, 15.26°, 17.25°, 18.08°, 18.92°, 20.88°, 21.99°, 23.41°, 24.09°, 25.07°, 25.38°, 25.99°, 26.66°, 27.17°, 28.38°, 29.41°, 29.98°, 30.70°, 31.02°, 31.72°, 33.67°, 35.40°, 36.35°, 36.74°, 37.26°, 38.53°, and 39.80°.
[0034] In some embodiments of the present invention, the XRPD pattern of the C-type crystals is essentially as shown in FIG. In some embodiments of the present invention, the XRPD pattern analysis data of the C-type crystal is as shown in Table 3. [Table 3]
[0035] In some embodiments of the present invention, the thermogravimetric analysis curve of the C-type crystals shows a weight loss of 1.21% at 200°C±3°C. In some embodiments of the present invention, the TGA pattern of the C-type crystals is as shown in FIG.
[0036] In some embodiments of the present invention, the differential scanning calorimetry curve of the C-type crystals has an onset value of one endothermic peak at 250.0°C ± 2°C. In some embodiments of the present invention, the DSC pattern of the C-type crystals is as shown in FIG.
[0037] The present invention provides a D-type crystal of the compound of formula (I), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.71±0.20°, 11.87±0.20°, and 25.21±0.20°. [ka]
[0038] In some embodiments of the present invention, the powder X-ray diffraction pattern of the D-type crystal has characteristic diffraction peaks at the following 2θ angles: 6.71±0.20°, 11.87±0.20°, 13.39±0.20°, 15.44±0.20°, 20.77±0.20°, 22.16±0.20°, 25.21±0.20°, and 27.05±0.20°.
[0039] In some embodiments of the present invention, the powder X-ray diffraction pattern of the D-type crystal has characteristic diffraction peaks at the following 2θ angles: 6.71±0.20°, 11.87±0.20°, 13.39±0.20°, 15.44±0.20°, 16.32±0.20°, 17.90±0.20°, 20.77±0.20°, 22.16±0.20°, 24.31±0.20°, 25.21±0.20°, 27.05±0.20°, and 27.41±0.20°.
[0040] In some embodiments of the present invention, the powder X-ray diffraction pattern of the D-type crystal is obtained by the following 2θ angles: 6.45°, 6.71°, 9.22°, 10.40°, 11.61°, 11.87°, 12.53°, 13.39°, 13.82°, 15.44°, 16.32°, 17.37°, 17.90°, 18.27°, 19.07°, 19.67°, 19.71°, 19.72 ... It has characteristic diffraction peaks at 90°, 20.77°, 22.16°, 24.31°, 25.21°, 26.10°, 27.05°, 27.41°, 28.50°, 29.59°, 30.10°, 30.89°, 31.17°, 32.81°, 33.77°, 34.17°, 35.52°, 36.57°, 38.20°, and 38.68°.
[0041] In some embodiments of the present invention, the XRPD pattern of the Form D crystal is essentially as shown in FIG. In some embodiments of the present invention, the XRPD pattern analysis data of the D-type crystal is as shown in Table 4. [Table 4]
[0042] In some embodiments of the present invention, the thermogravimetric analysis curve of the D-type crystals shows a weight loss of 1.14% at 200°C±3°C. In some embodiments of the present invention, the TGA pattern of the D-type crystal is as shown in FIG.
[0043] In some embodiments of the present invention, the differential scanning calorimetry curve of the D-type crystal has an onset value of one endothermic peak at 251.4°C ± 2°C. In some embodiments of the present invention, the DSC pattern of the D-type crystal is as shown in FIG.
[0044] The present invention provides type E crystals of the compound of formula (I), characterized in that the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 13.28±0.20°, 15.34±0.20°, and 25.14±0.20°. [ka]
[0045] In some embodiments of the present invention, the powder X-ray diffraction pattern of the E-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.11±0.20°, 13.28±0.20°, 15.34±0.20°, 18.16±0.20°, 22.06±0.20°, 25.14±0.20°, 26.75±0.20°, and 27.25±0.20°.
[0046] In some embodiments of the present invention, the powder X-ray diffraction pattern of the E-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.11±0.20°, 12.43±0.20°, 13.28±0.20°, 15.34±0.20°, 18.16±0.20°, 22.06±0.20°, 23.15±0.20°, and 25.14±0.20°.
[0047] In some embodiments of the present invention, the powder X-ray diffraction pattern of the E-type crystals has characteristic diffraction peaks at the following 2θ angles: 9.11±0.20°, 11.21±0.20°, 13.28±0.20°, 15.34±0.20°, 18.16±0.20°, 22.06±0.20°, 23.15±0.20°, 25.14±0.20°, 25.97±0.20°, 26.75±0.20°, 27.25±0.20°, and 30.82±0.20°.
[0048] In some embodiments of the present invention, the powder X-ray diffraction pattern of the E-type crystal has characteristic diffraction peaks at the following 2θ angles: 9.11±0.20°, 11.21±0.20°, 12.43±0.20°, 13.28±0.20°, 15.34±0.20°, 18.16±0.20°, 22.06±0.20°, 23.15±0.20°, 25.14±0.20°, 25.97±0.20°, 26.75±0.20°, and 27.25±0.20°.
[0049] In some embodiments of the present invention, the powder X-ray diffraction pattern of the E-type crystals has characteristic diffraction peaks at the following 2θ angles: 13.28±0.20°, 25.14±0.20°, and further at 15.34±0.20°, and / or 9.11±0.20°, and / or 10.94±0.20°, and / or 11.21±0.20°, and / or 12.43±0.20°, and / or 18.16±0.20°, and / or 22.06±0.20°, and / or 23.15±0.20°, and / or may have characteristic diffraction peaks at 23.35±0.20°, and / or 24.19±0.20°, and / or 25.97±0.20°, and / or 26.75±0.20°, and / or 27.25±0.20°, and / or 28.45±0.20°, and / or 29.49±0.20°, and / or 30.82±0.20°, and / or 33.74±0.20°, and / or 36.39±0.20°, and / or 37.34±0.20°, and / or 38.57±0.20°.
[0050] In some embodiments of the present invention, the powder X-ray diffraction pattern of the E-form crystals is at the following 2θ angles: 9.11±0.20°, 10.94±0.20°, 11.21±0.20°, 12.43±0.20°, 13.28±0.20°, 15.34±0.20°, 18.16±0.20°, 22.06±0.20°, 23.15±0.20°, 23.35±0.20°. , 24.19±0.20°, 25.14±0.20°, 25.97±0.20°, 26.75±0.20°, 27.25±0.20°, 28.45±0.20°, 29.49±0.20°, 30.82±0.20°, 33.74±0.20°, 36.39±0.20°, 37.34±0.20°, and 38.57±0.20°.
[0051] In some embodiments of the present invention, the powder X-ray diffraction pattern of the E-form crystals has characteristic diffraction peaks at the following 2θ angles: 9.11°, 10.94°, 11.21°, 12.43°, 13.28°, 15.34°, 17.39°, 18.16°, 20.18°, 18.94°, 20.95°, 22.06°, 23.15°, 23.35°, 24.19°, 25.14°, 25.97°, 26.75°, 27.25°, 28.45°, 29.49°, 30.16°, 30.82°, 33.74°, 35.45°, 36.39°, 37.34°, and 38.57°.
[0052] In some embodiments of the present invention, the XRPD pattern of the Form E crystals is essentially as shown in FIG. In some embodiments of the present invention, the XRPD pattern analysis data of the E-type crystal is as shown in Table 5. [Table 5]
[0053] In some embodiments of the present invention, the thermogravimetric analysis curve of the E-type crystals shows a weight loss of 0.79% at 200°C±3°C. In some embodiments of the present invention, the TGA pattern of the E-type crystals is as shown in FIG.
[0054] In some embodiments of the present invention, the differential scanning calorimetry curve of the E-type crystals has an onset value of one endothermic peak at 250.4°C ± 2°C. In some embodiments of the present invention, the DSC pattern of the E-type crystal is as shown in FIG.
[0055] The present invention further provides the use of Form A, Form B, Form C, Form D and Form E of the compound of formula (I) in the manufacture of a medicament for treating gout and hyperuricemia. (Effects of the Invention)
[0056] Crystals of the compound of formula (I) have stable physical properties and are not hygroscopic, and are therefore highly promising as a pharmaceutical.
[0057] Definitions and Explanations The following terms and phrases used herein shall have the following meanings unless otherwise specified. Certain words or terms, unless specifically defined, should not be considered indefinite or unclear, but should be understood according to their ordinary meaning. When trade names are mentioned herein, it is intended to refer to the corresponding trade name or its active ingredients.
[0058] The intermediate compounds of the present invention can be prepared by various synthetic methods known to those skilled in the art, including the specific embodiments listed below, embodiments formed by combination with other chemical synthetic methods, and equivalent substitution methods known to those skilled in the art, and preferred embodiments include, but are not limited to, the examples of the present invention.
[0059] The chemical reactions of the specific embodiments of the present invention are completed in a suitable solvent, which should be suitable for the chemical reactions of the present invention and the reagents and materials required therefor. To obtain the compounds of the present invention, those skilled in the art may need to modify or select synthetic steps or reaction schemes based on the existing embodiments.
[0060] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples in any way. All of the solvents used in this invention are commercially available and can be used without further purification.
[0061] Compounds are named according to conventional naming principles in the art or ChemDraw® software; commercially available compounds are named in the supplier's catalogue. The structure of the compound of the present invention can be confirmed by the usual methods known to those skilled in the art, and when the present invention relates to the absolute configuration of the compound, the absolute configuration can be confirmed by the usual technical means of those skilled in the art.For example, single crystal X-ray diffraction method (SXRD) is to collect diffraction intensity data of the cultivated single crystal with Bruker D8 venture diffractometer, the light source is CuKα radiation, the scanning method is φ / ω scanning, and after collecting relevant data, the crystal structure can be further analyzed by the direct method (Shelxs97) to confirm the absolute configuration.
[0062] The solvent used in the present invention can be obtained from commercial products. The following abbreviations are used in the present invention:-OMOM stands for methoxymethyl ether;HPE stands for 100% inhibitory activity;ZPE stands for 0% inhibitory activity;DPBS stands for Dulbecco's phosphate buffered saline.
[0063] The X-ray powder diffractometer (XRPD) method of the present invention Equipment model: Bruker D2 PHASER type X-ray diffraction equipment Detailed XRPD parameters are as follows: Source: Cu, k-Alphal (λ=1.54184 angstroms) Light-emitting tube voltage: 30 kV Light emitting tube current: 10mA Divergence slit: 0.6mm Soller slit in the main optical path axial direction: 2.5° Secondary path axial Soller slit: 2.5° Detector slit: 5.827° Anti-scattering slit: 0mm Scan axis: θs-θd Step size: 0.02 deg Dwell time per step: 0.2 seconds Scanning angle range: 3~40deg
[0064] Differential Scanning Calorimeter (DSC) Method of the Present Invention Instrument model: TA DSC Q2000 differential scanning calorimeter Test method: Take a sample (~1 mg), place it in a DSC aluminum crucible and test it at 50 mL / min N 2 Under these conditions, the sample is heated from 30° C. to 250° C. at a heating rate of 10° C. / min.
[0065] The Thermogravimetric Analysis (TGA) Method of the Present Invention Instrument model: DISCOVERY TGA 5500 Thermogravimetric Analyzer Test method: Take a sample (2-5 mg), place it in a TGA platinum crucible and test it at 25 mL / min N 2 Under these conditions, the sample is heated from room temperature to 300° C. at a heating rate of 10° C. / min.
[0066] Dynamic Vapor Sorption (DVS) Method of the Present Invention Equipment model: Intrinsic dynamic water vapor sorption equipment Test conditions: A sample (10-30 mg) is taken and placed on the DVS sample tray for testing. Detailed DVS parameters are as follows: Temperature: 25℃ Balance: dm / dt=0.002% / min (min: 10min, max: 180min) RH(%) test gradient: 10(90~0~90%), 5(90~95%) RH(%) test range: 0%~95%~0%
[0067] The classification of moisture absorption evaluation is as shown in Table 6 below. [Table 6] Note: ΔW% represents the increase in moisture weight of the test sample at 25±1℃ and 80±2% RH. [Brief description of the drawings]
[0068] [Figure 1] 1 is an XRPD pattern of Cu-Kα radiation of the A-type crystal of the compound of formula (I). [Diagram 2] 1 is a TGA pattern of crystals of type A of the compound of formula (I). [Diagram 3] 1 is a DSC pattern of crystal form A of the compound of formula (I). [Figure 4] 1 is an XRPD pattern of Cu-Kα radiation of the B-type crystal of the compound of formula (I). [Diagram 5] 1 is an XRPD pattern of Cu-Kα radiation of the C-type crystal of the compound of formula (I). [Figure 6] 1 is a TGA pattern of the C-type crystals of the compound of formula (I). [Figure 7] 1 is a DSC pattern of the C-type crystals of the compound of formula (I). [Figure 8] 1 is an XRPD pattern of Cu-Kα radiation of the D-type crystal of the compound of formula (I). [Figure 9] 1 is a TGA pattern of crystals of type D of the compound of formula (I). [Figure 10] 1 is a DSC pattern of the D-type crystals of the compound of formula (I). [Figure 11] 1 is an XRPD pattern of Cu-Kα radiation of E-type crystals of the compound of formula (I). [Figure 12] 1 is a TGA pattern of type E crystals of the compound of formula (I). [Figure 13] 1 is a DSC pattern of E-form crystals of the compound of formula (I). [Figure 14] 1 is a DVS pattern of the C-type crystals of the compound of formula (I). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0069] The present invention will be described in more detail below with reference to examples, which should not be construed as limiting the present invention in any way. The present invention has been described in detail herein, and specific embodiments thereof have also been disclosed. It is obvious to those skilled in the art that various modifications and improvements can be made to the specific embodiments of the present invention without departing from the spirit and scope of the present invention.
[0070] Example 1: Preparation of Crystalline Form A of the Compound of Formula (I) [ka]
[0071] Step 1: Synthesis of compound I-2 Potassium tert-butoxide (234.26 g, 2.09 mol) was added to dimethyl sulfoxide (1200 mL) and stirred at room temperature until clarified. Compound I-1 (200 g, 1.49 mol) in dimethyl sulfoxide (500 mL) was added dropwise at 15-20 ° C., and stirring was continued for 40 minutes after the dropwise addition was completed. Carbon disulfide (113.54 g, 1.49 mol, 90.11 mL) was added dropwise, and the temperature of the reaction solution was kept below 20 ° C., and stirring was continued for 20 minutes after the dropwise addition was completed. Potassium tert-butoxide (100.40 g, 894.70 mmol) was slowly added, and the temperature of the reaction solution was kept at 15-20 ° C. and stirred for 30 minutes. Next, ethyl bromoacetate (498.05 g, 2.98 mol, 329.83 mL) was added dropwise, and the temperature of the reaction solution was kept at 15-20 ° C. and stirred at this temperature for 1.5 hours. Potassium carbonate (206.09 g, 1.49 mol) was added, and the reaction solution was heated to 60 ° C. and stirred for 1.5 hours. 1 L of water was added to the reaction solution, the pH was adjusted to 3-4 with 6 M aqueous hydrochloric acid, extracted with ethyl acetate (1.5 L x 2), the combined organic phase was washed with saturated saline (200 mL x 3), the organic solvent was removed under reduced pressure, and the obtained crude product was added to isopropanol (200 mL), stirred uniformly, left for 15 hours, filtered, and dried in vacuum at 45 ° C. for 1 hour to obtain compound I-2. 1H NMR (400MHz, CDCl 3 ) δ: 4.32 (q, J = 7.2 Hz, 2H), 4.19 (q, J = 7.2 Hz, 2H), 3.56 (s, 2H), 3.25 (t, J = 6.8 Hz, 2H), 3.19 (t, J = 14.4 Hz, 2H), 2.26 - 2.17 (m, 2H), 1.37 (t, J = 7.2 Hz, 3H), 1.27(t, J = 7.2Hz, 3H). MS m / z= 364.8 [M+H] + .
[0072] Step 2: Synthesis of compound I-3 Compound I-2 (282 g, 773.82 mmol) was dissolved in ethanol (3.5 L), Raney nickel (99.45 g, 1.16 mol) was added, and the mixture was purged with nitrogen gas three times, and the mixture was reacted under hydrogen gas pressure of 2.5 MPA at 85° C. for 48 hours with stirring. The mixture was cooled and filtered through diatomaceous earth under nitrogen gas protection, and the filtrate was subjected to reduced pressure to remove the solvent to obtain compound I-3, which was used directly in the next step reaction without further purification. 1 H NMR (400MHz, CDCl 3 ) δ: 7.09 (s, 1H), 4.26 (q, J = 7.2 Hz, 2H), 3.20 (t, J = 6.8 Hz, 2H), 3.12 (t, J = 14.4 Hz, 2H), 2.20 - 2.10 (m, 2H), 1.30 (t, J = 6.8 Hz, 3H). MS m / z=247.0 [M+H] + .
[0073] Step 3: Synthesis of compound I-4 Compound I-3 (40.00 g, 162.42 mmol) was dissolved in methanol (200 mL), and 200 mL of an aqueous solution of sodium hydroxide (12.99 g, 324.84 mmol) was added. The reaction solution was heated to 50 ° C and stirred for 2 h. The organic solvent was removed under reduced pressure, and 150 mL of water was added to the residue. The pH was adjusted to 2-3 with 6 M aqueous hydrochloric acid, and a large amount of white solid precipitated. After filtration, the cake was washed with 100 mL of water, washed with 50 mL of petroleum ether, and dried in vacuum at 50 ° C for 3 h to obtain compound I-4. 1 H NMR (400MHz, CD 3 OD) δ: 7.38 (s, 1H), 3.33 - 3.17 (m, 4H), 2.28 - 2.21 (m, 2H).
[0074] Step 4: Synthesis of compound I-5 Compound I-4 (35.0 g, 160.39 mmol) was dissolved in tetrahydrofuran (200 mL), carbonyldiimidazole (33.81 g, 208.51 mmol) was added, the reaction solution was stirred under nitrogen gas protection for 2 hours, ammonia water (31.23 g, 240.58 mmol, 34.32 mL) was added, and the reaction solution was stirred for 15 hours. The organic solvent was removed under reduced pressure, and 300 mL of water was added to the resulting residue, stirred for 10 minutes, filtered, the cake was washed with 100 mL of water, and dried under vacuum at 55 ° C for 2.5 hours to obtain compound I-5. 1 H NMR (400MHz, CDCl 3 ) δ: 7.09 (s, 1H), 5.72 (brs, 2H), 3.30 - 3.18 (m, 4H), 2.29 - 2.19 (m, 2H).
[0075] Step 5: Synthesis of compound I-6 Compound I-5 (31 g, 142.70 mmol) was dissolved in N,N-dimethylformamide (200 mL), N-bromosuccinimide (27.94 g, 156.97 mmol) was added slowly in batches, and the reaction solution was kept stirring for 2 h at 20° C. The reaction solution was slowly poured into 600 mL of stirred water, a large amount of solid precipitated, stirred for 10 min, filtered, the cake was washed with 200 mL of water, washed with 100 mL of petroleum ether, and dried in vacuum at 50° C. for 2 h to obtain compound I-6. 1 H NMR (400MHz, CDCl 3 ) δ: 5.62 (brs, 2H), 3.25 (t, J = 7.2 Hz, 2H), 3.04 (t, J = 14.0 Hz, 2H), 2.26 - 2.18 (m, 2H).
[0076] Step 6: Synthesis of compound I-7 Compound I-6 (48 g, 162.09 mmol) and triethylamine (32.80 g, 324.18 mmol, 45.12 mL) were added to ethyl acetate (250 mL), cooled to 0 ° C under nitrogen gas protection, trifluoroacetic anhydride (44.26 g, 210.72 mmol, 29.31 mL) was added dropwise, the reaction solution was stirred at this temperature for 1 hour, and the temperature was raised to 20 ° C and stirring was continued for 0.5 hours. The reaction solution was diluted with 250 mL of ethyl acetate, washed with water (100 mL × 2), saturated sodium bicarbonate solution (150 mL) and saturated saline (100 mL) in sequence, dried over anhydrous sodium sulfate, filtered, and the organic solvent was removed under reduced pressure to obtain compound I-7, which was used directly in the next step reaction without further purification. 1 H NMR (400MHz, CDCl 3 ) δ: 3.13 - 2.97 (m, 4H), 2.30 - 2.20 (m, 2H).
[0077] Step 7: Synthesis of compound I-8 Compound I-7 (6.0 g, 21.57 mmol), compound I-7-1 (7.60 g, 23.73 mmol), and anhydrous potassium phosphate (9.16 g, 43.15 mmol) were added to ethylene glycol dimethyl ether (60 mL) and water (12 mL), and the mixture was heated under nitrogen gas protection with Pd(dppf)Cl 2 (394.64 mg, 539.34 μmol) was added, and the reaction solution was heated to 85° C. under nitrogen gas protection and stirred for 15 hours. After cooling, 20 mL of water and 100 mL of ethyl acetate were added to the reaction solution, stirred for 10 minutes, filtered, the organic phase was separated from the filtrate, the aqueous phase was extracted with ethyl acetate (30 mL×3), the combined organic phase was washed with saturated saline (30 mL), dried over anhydrous sodium sulfate, filtered, and the organic solvent was removed under reduced pressure. The obtained crude product was added to ethyl acetate (80 mL), and activated carbon (4 g) and silica gel for removing palladium (4 g) were added in sequence, heated to 80° C. and stirred for 1 hour, cooled, filtered through diatomaceous earth, and the organic solvent was removed under reduced pressure. The obtained crude product was subsequently slurried with tert-butyl methyl ether (25 mL) at 25° C. for 0.5 hours, filtered, and the obtained cake was dried under vacuum at 45° C. for 1 hour to obtain compound I-8. 1 H NMR (400MHz, CDCl 3 ) δ: 11.18 (s, 1H), 7.86 (d, J = 8.0 Hz, 1H), 7.01 (d, J = 1.6 Hz, 1H), 6.92 - 6.90 (m, 1H), 3.24 (t, J = 14.4 Hz, 2H), 3.12 (t, J = 6.8Hz, 2H), 2.36 - 2.26 (m, 2H), 1.64 (s, 9H).
[0078] Step 8: Synthesis of Crystalline Form A of Compound of Formula (I) Compound I-8 (32 g, 81.75 mmol) was added to trifluoroacetic acid (250 mL), and the reaction solution was stirred at 20° C. for 1 hour to react. Trifluoroacetic acid was removed under reduced pressure, and water (300 mL) was added to the resulting residue, which was slurried at room temperature for 20 minutes until completely dispersed, filtered, and the cake was washed with water (200 mL) and dried under vacuum at 45° C. for 1 hour to obtain A-type crystals of the compound of formula (I). 1 H NMR (400MHz, CD 3 OD) δ: 8.03 - 7.96 (m, 1H), 7.12 - 7.06 (m, 2H), 3.36 - 3.29 (m, 2H), 3.16 - 3.07 (m, 2H), 2.44 - 2.30 (m, 2H). The XRPD pattern of the A-type crystal is shown in Figure 1, the TGA pattern in Figure 2, and the DSC pattern in Figure 3.
[0079] Example 2: Preparation of Compounds of Formula (I) [ka]
[0080] Step 1: Synthesis of compound I-4 Compound I-3 (2.5 g, 10.15 mmol) was dissolved in methanol (10 mL), and then water (10 mL) and sodium hydroxide (1.62 g, 40.61 mmol) were added. The resulting reaction solution was placed in a 40°C oil bath and stirred for 2 hours to react. The reaction solution was concentrated under reduced pressure to remove half of the solution, and water (5 mL) was added to the residue. The pH was adjusted to 2-3 with 6M hydrochloric acid while stirring, and a large amount of white solid precipitated. The solid was collected by filtration and dried in vacuum at 50°C for 3 hours to obtain compound I-4. 1 H NMR (400MHz, CDCl 3 ) δ: 7.28 (s, 1H), 3.30 (t, J=7.0 Hz, 2H), 3.22 (t, J=14.3 Hz, 2H), 2.25 (tt, J=6.8, 13.4 Hz, 2H).
[0081] Step 2: Synthesis of compound I-5 Compound I-4 (500 mg, 2.29 mmol) was dissolved in dichloromethane (5 mL), then carbonyldiimidazole (445.83 mg, 2.75 mmol) was added, and the resulting reaction solution was stirred and reacted under nitrogen gas protection for 1 hour, and then the reaction solution was poured into vigorously stirred ammonia water (2.87 g, 22.91 mmol, 3.15 mL, content: 28%) in tetrahydrofuran (5 mL) and stirred and reacted for 30 minutes. The reaction solution was concentrated under reduced pressure at 25 ° C, the residue was extracted with ethyl acetate (20 mL × 3), the organic phase was combined, and spin-dried to obtain the crude product. The crude product was subjected to silica gel column chromatography (ethyl acetate / petroleum ether = 0 ~ 45%) to obtain compound I-5. 1 H NMR (400MHz, CDCl 3 ) δ: 7.10 (s, 1H), 5.58 (br s, 2H), 3.28 (t, J=6.9 Hz, 2H), 3.21 (t, J=14.4 Hz, 2H), 2.24 (tt, J=6.9, 13.4 Hz, 2H).
[0082] Step 3: Synthesis of Compounds 2-4 Compound I-5 (320 mg, 1.47 mmol) was dissolved in DMF (3 mL), the resulting solution was cooled to 0 ° C, then cyanuric chloride (298.81 mg, 1.62 mmol) was added, and the final reaction solution was stirred and reacted under nitrogen gas protection for 2 hours (at this time, a large amount of white solid precipitated). The reaction solution was diluted with ethyl acetate (50 mL), then washed with water (10 mL × 3) and saturated saline (10 mL), the organic phase was dried with an appropriate amount of anhydrous sodium sulfate, and filtered to remove the drying agent. The filtrate was reduced pressure to remove the solvent to obtain the crude product compound 2-4, which was used directly in the next step reaction. 1 H NMR: (400MHz, CDCl 3 ) δ: 7.25 (s, 1H), 3.21 (t, J=14.3 Hz, 2H), 3.09 (t, J=6.9 Hz, 2H), 2.28 (tt, J=6.8, 13.2 Hz, 2H).
[0083] Step 4: Synthesis of Compounds 2-5 Compound 2-4 (290 mg, 1.46 mmol) was dissolved in acetic acid (2 mL), then liquid bromine (348.94 mg, 2.18 mmol, 112.56 μL) was added, and the resulting reaction solution was stirred at room temperature of 25 ° C for 15 hours to react. The reaction solution was spin-dried, and ethyl acetate (30 mL) was added to the residue, then the pH was adjusted to 7-8 with saturated sodium carbonate, the organic phase was separated, and the aqueous phase was extracted with ethyl acetate (30 mL). The organic phases were combined and concentrated under reduced pressure to obtain the crude product. The crude product was subjected to silica gel column chromatography (ethyl acetate / petroleum ether = 0-5%) to obtain compound I-7. 1 H NMR: (400MHz, CDCl 3 ) δ:3.10-2.99 m, 4H), 2.32-2.19 (m, 2H).
[0084] Step 5: Synthesis of Compounds 2-6 Compound I-7 (140 mg, 503.39 μmol), borate ester 2-5A (178.39 mg, 553.73 μmol), potassium carbonate (139.14 mg, 1.01 mmol) were added to dioxane (3 mL) and water (0.6 mL), and then [1,1'-bis(diphenylphosphino)ferrocene]dichloropalladium(II) (Pd(dppf)Cl 2 ) (36.83 mg, 50.34 μmol) was added, and the mixture was placed in an oil bath at 105° C. under nitrogen gas protection and reacted with stirring for 15 hours. The reaction solution was spin-dried to obtain a crude product, which was then subjected to silica gel column chromatography (ethyl acetate / petroleum ether=0-25%) to obtain compound 2-6. 1 H NMR: (400MHz, CHCl 3 ) δ: 7.87 (d, J=8.0 Hz, 1H), 7.28 (d, J=1.6 Hz, 1H), 7.10 (dd, J=1.6, 8.0 Hz, 1H), 5.0 (s, 2H), 3.3 (s, 3H), 3.55(s, 3H), 3.23 (t, J=14.4 Hz, 2H), 3.13 (t, J=6.8 Hz, 2H), 2.39-2.24 (m, 2H).
[0085] Step 6: Synthesis of Compounds 2-7 Compound 2-6 (105 mg, 266.90 μmol) was dissolved in tetrahydrofuran (2 mL), then lithium hydroxide monohydrate aqueous solution (2 M, 533.80 μL) was added, and the resulting reaction solution was stirred at room temperature 25 ° C for 15 hours to react. Tetrahydrofuran was removed from the reaction solution by spinning at 40 ° C, and the pH of the residue was adjusted to 2-3 with 2 M hydrochloric acid, and a large amount of solid was precipitated. Ethyl acetate (50 mL) was added and stirred, and the ethyl acetate was separated and spin-dried to obtain compound 2-7. The crude product was directly used in the next step reaction.
[0086] Step 7: Synthesis of Compounds of Formula (I) Compound 2-7 (105 mg, 276.77 μmol) was dissolved in methanol (1 mL), then hydrochloric acid (60.55 mg, 1.66 mmol, 59.36 μL) was added, the reaction solution became cloudy, and the mixture was stirred at 25 ° C for 3 hours to react. The reaction solution was spin-dried at 40 ° C, and the resulting residue was separated and purified by preparative high-performance liquid chromatography (chromatography column: Venusil ASB Phenyl 150 × 30 mm × 5 μm; mobile phase: [water (0.05% HCl)-ACN]; ACN%: 60% ~ 90%, 9 min) to obtain the compound of formula (I). 1 H NMR (400MHz, CD 3 MS (ESI) m / z: 334.02 [MH] - .
[0087] Example 3: Preparation of B-type crystals of the compound of formula (I) The A-type crystals of the compound of formula (I) (20 mg, 0.06 mmol) were added to dichloromethane (1 mL) and then stirred at 25° C. for 120 hours. After filtration, the cake was dried in vacuum at 50° C. for 2 to 5 hours to obtain the B-type crystals of the compound of formula (I). The XRPD pattern of the B-type crystals is shown in FIG. 4.
[0088] Example 4: Preparation of C-type crystals of the compound of formula (I) The A-type crystals of the compound of formula (I) (1.0 g, 2.98 mmol) were added to a mixed solvent of ethyl acetate (5 mL) and n-heptane (5 mL), and then stirred at 25° C. for 72 hours. After filtration, the cake was dried in vacuum at 45° C. for 2 hours to obtain the C-type crystals of the compound of formula (I). The XRPD pattern of the C-type crystals is shown in FIG. 5, the TGA pattern in FIG. 6, and the DSC pattern in FIG. 7.
[0089] Example 5: Preparation of D-type crystals of the compound of formula (I) Approximately 20 mg of the A-type crystals of the compound of formula (I) were weighed and added to a mixed solvent of tetrahydrofuran (0.4 mL) and water (0.4 mL), and the mixed solution was stirred at 50° C. until the solids dissolved, cooled to 13° C., and stirred for 72 hours. After filtration, the cake was vacuum dried at 45° C. for 2 hours to obtain the D-type crystals of the compound of formula (I). The XRPD pattern of the D-type crystals is shown in FIG. 8, the TGA pattern in FIG. 9, and the DSC pattern in FIG. 10.
[0090] Example 6: Preparation of E-type crystals of the compound of formula (I) The A-type crystals of the compound of formula (I) (1.0 g, 2.98 mmol) were added to a mixed solvent of tetrahydrofuran (3.3 mL) and water (6.6 mL), and the resulting mixture was stirred at 25° C. for 72 hours. After filtration, the cake was dried in vacuum at 45° C. for 2 hours to obtain the E-type crystals of the compound of formula (I). The XRPD pattern of the E-type crystals is shown in FIG. 11, the TGA pattern in FIG. 12, and the DSC pattern in FIG. 13.
[0091] Example 7: Hygroscopicity study of crystal form C of compound of formula (I) Test materials: DVS Intrinsic Dynamic Vapor Sorption Apparatus Testing Method: Take 10-30 mg of type C crystals of the compound of formula (I) and place it on a DVS sample tray for testing.
[0092] Test Results: The DVS pattern of the C-type crystals of the compound of formula (I) is shown in FIG. 14, with ΔW=0.196%. Test conclusion: The hygroscopic weight gain of the C-type crystals of the compound of formula (I) at 25° C. and 80% RH is 0.196%, which indicates that the compound is not hygroscopic.
[0093] Example 8: Solid-state stability test of C-type crystals of the compound of formula (I) In accordance with the "Guiding Principles for Stability Testing of Drug Substances and Preparations" (Chinese Pharmacopoeia, 2015 Edition, Part IV, General Principle 9001), the stability of the C-type crystals of compound of formula (I) under conditions of high temperature (60°C, open), high humidity (room temperature / relative humidity 92.5%, open) and strong light exposure (5000 lx, closed) was examined.
[0094] 12 parts of the C-type crystals of the compound of formula (I) were weighed in parallel, about 1.5 g per part, and placed in a flat weighing bottle (70 x 35 mm) or a disposable petri dish and spread into a thin layer. Each was placed under high temperature (60°C), high humidity (25°C / 92.5% humidity), high temperature and high humidity (40°C / 75% humidity) and light irradiation stability conditions. The samples placed under high temperature and high humidity conditions had the mouth of the bottle sealed with aluminum foil and several small holes were made in the aluminum foil to allow the samples to be in complete contact with the surrounding air, and the samples placed under strong light irradiation conditions were sealed with a quartz glass lid. Samples placed under high temperature (60°C) and high humidity (92.5% humidity, room temperature) conditions were sampled and tested (appearance, related substances and content) on the 5th and 10th days, samples placed under high temperature and high humidity (40°C / 75% humidity) conditions were sampled and tested (appearance, related substances and content) on the 1st, 2nd and 3rd months, and samples placed under light irradiation conditions were sampled and tested (appearance, related substances and content) on the 1st, 2nd and 3rd months. 6When the Lux·hr was reached, samples were taken and tested, and the test results were compared to the initial test results on Day 0, with the test results shown in Table 7 below: [Table 7] Conclusion: The C-type crystal of compound of formula (I) has good stability under the influencing factors of high temperature, high humidity, strong light irradiation and accelerated conditions.
[0095] Biological Test Data: Experimental Example 1: Xanthine oxidase inhibitory activity test 1. Purpose of the experiment The aim is to assess the inhibitory level of compounds on xanthine oxidase activity. 2. Reagents The main reagents used in this study are xanthine (Sigma, product number: X4002-1G, batch number: SLBB5664V) and xanthine oxidase (Sigma, product number: X4376-5UN, batch number: SLBQ1518V). 3.Equipment The main equipment used in this study is a multifunction microplate reader.
[0096] 4. Experimental Method 1) 50 μL of Dulbecco's Phosphate Buffered Saline (DPBS) was added to compound background control wells and HPE (100% inhibitory activity) positive control wells. 2) 2 U / mL xanthine oxidase was diluted to 0.04 U / mL with DPBS and 50 μL of xanthine oxidase was added to compound activity test wells and ZPE (0% inhibitory activity) negative control wells. 3) Compounds were diluted 8 points in a 3-fold gradient with DMSO, then compounds were diluted with DPBS and 50 μL was added to each well in triplicate wells. 50 μL of DPBS was added to each well of HPE (100% inhibitory activity) positive control wells and ZPE (0% inhibitory activity) negative control wells. 4) 200 mM xanthine was diluted to 300 μM with DPBS. 100 μL of xanthine was added to each well and reacted at room temperature for 30 minutes, the final concentration of xanthine oxidase in each well was 0.01 U / mL, and the final concentration of DMSO in each well was 0.5%. HPE (100% inhibitory activity) positive control wells contained xanthine but no xanthine oxidase, ZPE (0% inhibitory activity) negative control wells contained xanthine and xanthine oxidase, and compound background control wells contained various concentrations of compound and xanthine but no xanthine oxidase. 5) The absorbance at 290 nm was detected by a spectrophotometer. 6) Data analysis: The inhibition rate of each well against xanthine oxidase was calculated according to the following formula.
[0097]
number
[0098] 5. Experimental Results The experimental results are shown in Table 8. [Table 8] Experimental conclusion: The compounds of the present invention have good xanthine oxidase inhibitory activity.
[0099] Experimental Example 2: Inhibitory activity test of compounds against uric acid uptake 1. Purpose of the experiment In this study, a cell line stably transfected with the human Urat1 gene was used to evaluate the inhibitory activity of test compounds on uric acid uptake.
[0100] 2. Experimental Materials 2.1 Cell lines A cell line stably transfected with human Urat1 gene was constructed by Wuxi APPTEC (Shanghai) Co., Ltd. A cell line stably transfected with human Urat1 gene (Urat1-MDCK) was obtained by transfecting human Urat1 gene into MDCK cells and screening with G418. The cell line was cultured in MEM medium containing 10% fetal bovine serum (FBS), 100 U / ml penicillin, 100 μg / ml streptomycin, 2 mM L-glutamine, 1% non-essential amino acids, and 250 μg / ml G418. 2.2 Reagents The main reagent used in this study is 14C-uric acid (ARC, product number: ARC-0513, batch number: 200122). 2.3 Equipment The main instrument used in this study was a liquid scintillation analyzer (Perkin Elmer, Tri-Carb 4910TR).
[0101] 3. Experimental Method 3.1 Cell plating 3.1.1 Urat1-MDCK cells cultured in a T150 cell culture flask were digested with 0.25% trypsin and then diluted with fresh medium to adjust the suspension to 200,000 cells / ml. 3.1.2 Cells were seeded into 48-well cell culture plates at 0.5 ml per well, with a final cell density of 100,000 cells / well. 3.1.3 Keep the cell culture plate at 37 °C and 5% CO 2 The plate was placed in an incubator and cultured overnight. 3.2 Compound processing and detection 3.2.1 Compounds were diluted in DMSO in a 5-fold gradient to 4 points, and the diluted concentrations were 200-fold higher than the final detection concentration. Compounds were then diluted 10-fold in HBSS buffer. 3.2.2 10 mM concentrated stock solution of 14C-uric acid was diluted to 1 mM with HBSS buffer. 3.2.3 After culturing the cell culture plate overnight, the cell culture medium in the culture plate was removed, the cells were washed three times with HBSS buffer, and 90 μl of HBSS buffer was added to each well. 3.2.4 5 μl of diluted compound is added to each well and the cells are incubated at 37°C, 5% CO 2 The plate was placed in an incubator and incubated for 20 minutes. The DMSO content in each well was 0.5%. Test compound (10 μM) was used as a 100% inhibition control, and 0.5% DMSO was used as a 0% inhibition control. 3.2.5 5 μl of diluted 14C-uric acid was added to each well of the cell plate, so that the final concentration of uric acid in each well was 50 μM. The cells were incubated at 37°C, 5% CO 2 The cells were placed in an incubator and incubated for 15 minutes, then washed three times with pre-chilled HBSS buffer. 3.2.6 150 μl of 0.1 M NaOH was added to each well and cells were allowed to lyse for 10 minutes. 3.2.7 Cell lysates were collected in liquid scintillation detection bottles and 2ml of scintillation fluid was added to each bottle for detection. 3.2.8 The 14C content of each tube sample was detected by a liquid scintillation analyzer. 3.2.9 Data Analysis:
number
[0102] 4. Experimental Results The experimental results are shown in Table 9. [Table 9] Experimental conclusion: The compounds of the present invention have good uric acid uptake inhibitory activity.
[0103] Experimental Example 3: Metabolic Stability in Hepatocytes (HMS) Study 1. Purpose of the experiment To test the metabolic stability of test compounds in human and rat hepatocytes.
[0104] 2. Experimental Materials 2.1 Test compound (10 mM), control compounds: 7-ethoxycoumarin (30 mM), 7-hydroxycoumarin (30 mM) 2.2 Cells Cell information is shown in Table 10. [Table 10] 2.3 Buffer system: Thawing medium: William's medium E contains 5% fetal bovine serum and 30% Percoll solution and other supplementary compounds. Culture medium: Williams' medium E (phenol red-free) containing 2 mM L-glutamine and 25 mM 2-[4-(2-hydroxyethyl)-1-piperazinyl]ethanesulfonic acid. Stop solution: acetonitrile containing 200 ng / mL tosylamide and labetalol as internal standards. Diluent: ultrapure water.
[0105] 3. Experimental Method 1) A precise amount of positive control compound was dissolved in dimethylsulfoxide (DMSO) to prepare a 30 mM solution. 2) 10 mM test compound and 30 mM positive control compound were diluted to 1 mM and 3 mM in DMSO on a 96-well plate. 3) 1 mM test compound and 3 mM positive control compound were diluted in acetonitrile to 100 μM and 300 μM working solutions. 4) Thaw the frozen cells, separate them, suspend them in medium, and then soak them in pre-warmed medium at 0.5 × 10 6 Diluted to cells / mL. 5) 198 μL of the pre-warmed cell suspension was added to a 96-well plate. 6) 100 μL of stop solution was transferred to a set of pre-labeled 96-well plates (acetonitrile containing 200 ng / mL tosylamide and 200 ng / mL labetalol as internal standards). 7) 2 μL of 100 μM test compound or 300 μM positive control titration solution was added in duplicate to each well of a 96-well plate. 8) For TO samples, mix for approximately 1 minute until a uniform suspension was formed, then immediately transfer 20 μL of each sample to a well containing 100 μL of ice-cold stop solution and mix. 9) Store all plates in a humidified incubator with 5% CO 2 The mixture was incubated at 37°C and the reaction was started with a constant shaking speed of about 600 rpm. 10) Samples were mixed at 15, 30, 60, and 90 minutes, then 20 μL of each sample at each time point was transferred to wells containing 100 μL of ice-cold stop solution and mixed. 11) Media control (MC) sample plates (labeled T0-MC and T90-MC) were prepared at T0 and T90 by adding the same components to each well except for the cell suspension. A final concentration table was created. 12) At each corresponding time point, the plate was removed from the incubator and mixed with 100 μL of ice-cold stop solution to terminate the reaction. 13) The plates were immediately vortexed on a plate shaker at 500 rpm for 10 minutes. Then, all sample plates were centrifuged at 3220xg for 20 minutes at 4°C. 14) After centrifugation, 35 μL / well of the sample plate supernatant was transferred to another set of pre-labeled 96-well plates containing 70 μL of ultrapure water. 15) The analysis plate was sealed and stored at 4°C until LC-MS-MS analysis. The remaining ratios of the test compound and the control compound were calculated according to the following formula.
number
[0106] 4. Experimental Results The results are shown in Table 12. [Table 12] Experimental Conclusion: The compounds of the invention are moderately cleared in human hepatocytes and highly cleared in rat hepatocytes.
[0107] Experimental Example 4. Membrane permeability MDR1 test 1. Purpose of the experiment: MDR1-MDCK II cells are Madin-Darby canine kidney cells transfected with human MDR1 gene, which can stably and highly express P-gp. The aim of this study is to test the bidirectional permeability of compounds across the MDR1-MDCK II cell model and evaluate whether the compounds can be effluxed and transported to the outside.
[0108] 2. Cell culture: MDR1-MDCK II cells (obtained from Piet Borst, Netherlands Cancer Institute) were cultured at 2.5 × 10 5 The cells were seeded onto polyethylene membranes (PET) of a 96-well insert system at a density of 1000 cells / mL, and a confluent cell monolayer was formed on days 4–7.
[0109] 3. Experimental Method Test compounds were diluted in transport buffer (HBSS, 10 mM Hepes with DMSO, pH: 7.4) at a concentration of 2 μM (DMSO<1%) and coated on the apical or basolateral side of the cell monolayer. Test compounds in A to B or B to A directions were tested in duplicate, digoxin was tested at 10 μM in A to B or B to A directions, nadolol and metoprolol were tested at 2 μM in A to B directions, and the plates were incubated at 37±1°C in CO 2 In an incubator with saturated humidity and 5% CO 2 The plates were incubated in 5% CO for 2.5 h without shaking and the efflux ratio of each compound was measured and quantified for the test and reference compounds. Analysis was performed by LC / MS / MS based on the peak area ratio of analyte / IS. After transport measurements, the integrity of the cell monolayer was determined using a Lucifer Yellow rejection measurement. The buffer was removed from the apical and basolateral chambers, then 75 μL of 100 μM Lucifer Yellow was added in transport buffer, respectively, and 250 μL of transport buffer was added to the apical and basolateral chambers. The plates were incubated at 37°C and 5% CO 2 The plates were incubated at 4°C for 30 min at 200°C and saturated humidity without shaking. After 30 min of incubation, 20 μL of Lucifer Yellow sample was taken from the apical side, followed by the addition of 60 μL of transport buffer. Then, 80 μL of Lucifer Yellow sample was taken from the basolateral side. The relative fluorescence units (RFU) of Lucifer Yellow were measured at 425 / 528 nm (excitation / emission) using an Envision microplate reader.
[0110] 4. Data Calculation The apparent permeability coefficient (P app , cm / s), external extraction rate, and recovery rate were calculated. Apparent permeability coefficient (P app , cm / s) is calculated using the following formula: P app =(dC r / d t )×V r / (A×C 0 ) dC r / d t is the cumulative concentration of the compound at the receiving end per unit time (μM / s), and V ris the volume of the solution at the receiving end (the solution volumes at the apical and basal ends are 0.075 mL and 0.250 mL, respectively), and A is the relative surface area of the cell monolayer (0.0804 cm 2 ) and C 0 is the initial concentration of the test substance at the dosing end (nM) or the peak area ratio of the reference substance.
[0111] The external exclusion ratio is calculated using the following formula: Exclusion ratio=P app (BA) / P app (AB) The recovery rate is calculated using the following formula: % recovery rate=100×[(V r ×C r )+(V d ×C d )] / (V d ×C 0 ) C 0 is the initial concentration of the test substance at the dosing end (nM) or the peak area ratio of the reference substance, and V d is the volume of the dosing end (apical end is 0.075 mL, basal end is 0.250 mL), and C d and C r are the final concentrations (nM) of the test substance or the peak area ratio of the reference substance at the dosing end and the receiving end, respectively. The percentage of Lucifer Yellow in the basolateral wells is calculated using the following formula:
number
[0112] 5. Experimental Results The results are shown in Table 13. [Table 13] Experimental conclusion: The compounds of the present invention are highly permeable compounds.
[0113] Experimental Example 5: Cytochrome P450 isoenzyme inhibitory activity test 1. Purpose of the experiment The objective of the present invention is to determine the inhibitory activity of test compounds against different isoforms of human cytochrome P450 isozymes.
[0114] 2. Experimental Method Test compound, standard inhibitor (final concentration 100 times) and mixed substrate working solutions were prepared, and frozen microsomes (purchased from Corning Inc.) were taken out and thawed in a -80 ° C refrigerator. 20 μL of test compound and standard inhibitor solutions were added to the corresponding wells, and at the same time, 20 μL of the corresponding solvent was added to the control wells without inhibitors (NIC) and blank control wells (Blank). Then, 20 μL of mixed substrate solution was added to the corresponding wells except the blank wells (20 μL of phosphate buffer (PB) was added to the blank wells). Human liver microsome solution was prepared (after use, date was written and returned to the refrigerator immediately), and then 158 μL of human liver microsome solution was added to all wells. The above sample plate was pre-incubated in a 37 ° C water bath, and coenzyme factor (NADPH) solution was prepared. After 10 minutes, 20 μL of NADPH solution was added to all wells, and the sample plate was shaken well and then incubated in a 37 ° C water bath for 10 minutes. At the corresponding time points, 400 μL of cold acetonitrile solution (internal standards were 200 ng / mL tolbutamide and labetalol) was added to terminate the reaction. The sample plate was mixed well and then centrifuged at 4000 rpm for 20 min to precipitate the proteins. 200 μL of the supernatant was taken and added to 100 μL of water, shaken well and detected by LC / MS / MS.
[0115] 3. Experimental Results The results are shown in Table 14. [Table 14] Experimental Conclusion: The compounds of the present invention have very low inhibitory activity against CYP1A2, CYP2C19, CYP2D6 and CYP3A4-M, and moderate inhibitory activity against CYP2C9.
[0116] Experimental Example 6: Pharmacokinetics in SD rats 1. Purpose of the experiment: To study the pharmacokinetics of the test compound in SD rats.
[0117] 2. Experimental materials: Sprague Dawley rats (male, 180-350g, 6-10 weeks old, Beijing Vital River Laboratory Animal Technology Co., Ltd.)
[0118] 3. Experimental Method: The compound was mixed with 5% DMSO / 10% Solutol / 85% water, stirred and vortexed to prepare a clear solution of 0.6 mg / mL, which was used for administration of the injection group, and filtered through a microporous membrane for use. The compound was mixed with 5% DMSO / 10% Solutol / 85% water, stirred and vortexed to prepare a clear solution of 1 mg / mL, which was used for oral administration. Six male SD rats were divided into two groups. The animals in group 1 were administered a single intravenous dose of 3 mg / kg, the solvent was 5% DMSO / 10% Solutol / 85% water, and the dose was 5 mL / kg. The animals in group 2 were administered a single intragastric oral dose of 10 mg / kg of the test compound, the oral solvent was 5% DMSO / 10% Solutol / 85% water, and the oral dose was 10 mL / kg. Whole blood was collected at 0 hours (intragastric administration group only), 0.083 hours (intravenous administration group only), 0.25 hours, 0.5 hours, 1 hour, 2 hours, 4 hours, 8 hours, and 24 hours after administration. Plasma was obtained by centrifuging whole blood at 3200 g for 10 minutes at 4°C. The concentrations of the compounds and uric acid in plasma (intragastric administration group only) were measured by LC / MS / MS, and pharmacokinetic parameters such as peak concentration, peak time, clearance rate, half-life, area under the drug concentration-time curve, and bioavailability were calculated using Phoenix WinNonlin software.
[0119] The experimental results are shown in Table 15 below. [Table 15] Experimental Conclusion: The compounds of the present invention have good pharmacokinetic properties and high oral bioavailability. 0 is the initial concentration, T 1 / 2 is the elimination half-life, and Vd ss is the apparent volume of distribution at steady state, Cl is the total clearance rate, and AUC 0-last is the area under the plasma concentration-time curve from time 0 to the last quantifiable time point, AUC 0-inf is the area under the plasma concentration-time curve when extrapolated from time 0 to infinity, and C max is the peak concentration and Tmax is the time when blood concentration peaks.
Claims
1. A C-type crystal of the compound of formula (I), having a powder X-ray diffraction pattern having characteristic diffraction peaks at the following 2θ angles: 13.20±0.20°, 15.26±0.20°, 18.08±0.20°, 21.99±0.20°, 25.07±0.20°, 25.38±0.20°, 26.66±0.20°, and 30.70±0.20°. 【Chemistry 1】
2. The C-type crystal according to claim 1, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 9.03±0.20°, 13.20±0.20°, 15.26±0.20°, 18.08±0.20°, 21.99±0.20°, 25.07±0.20°, 25.38±0.20°, 26.66±0.20°, 28.38±0.20°, 29.41±0.20°, 30.70±0.20°, and 38.53±0.20°.
3. The C-type crystal according to claim 2, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 13.20°, 15.26°, 18.08°, 21.99°, 25.07°, 25.38°, 26.66°, and 30.70°.
4. The C-type crystal according to claim 3, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 5.66°, 9.03°, 11.13°, 13.20°, 13.70°, 15.26°, 17.25°, 18.08°, 18.92°, 20.88°, 21.99°, 23.41°, 24.09°, 25.07°, 25.38°, 25.99°, 26.66°, 27.17°, 28.38°, 29.41°, 29.98°, 30.70°, 31.02°, 31.72°, 33.67°, 35.40°, 36.35°, 36.74°, 37.26°, 38.53°, and 39.80°.
5. A C-type crystal described in any one of claims 1 to 4, wherein the analytical data of the XRPD pattern of the C-type crystal is as shown in the table below. 【Table 1】
6. The C-type crystal according to any one of claims 1 to 4, wherein the weight loss reaches 1.21% at 200°C ± 3°C in a thermogravimetric analysis curve.
7. The C-type crystal according to any one of claims 1 to 4, wherein a differential scanning calorimetry curve has an onset value of one endothermic peak at 250.0°C ± 2°C.
8. The powder X-ray diffraction pattern has the following 2θ angles: 9.11±0.20°, 12.43±0.20° The E-type crystal of the compound of formula (I) has characteristic diffraction peaks at 13.28±0.20°, 15.34±0.20°, 18.16±0.20°, 22.06±0.20°, 23.15±0.20°, and 25.14±0.20°. 【Chemistry 2】
9. The E-type crystal according to claim 8, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 9.11 ± 0.20 °, 11.21 ± 0.20 °, 12.43 ± 0.20 °, 13.28 ± 0.20 °, 15.34 ± 0.20 °, 18.16 ± 0.20 °, 22.06 ± 0.20 °, 23.15 ± 0.20 °, 25.14 ± 0.20 °, 25.97 ± 0.20 °, 26.75 ± 0.20 °, and 27.25 ± 0.20 °.
10. The E-type crystal according to claim 9, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 9.11°, 12.43°, 13.28°, 15.34°, 18.16°, 22.06°, 23.15°, and 25.14°.
11. The E-type crystal according to claim 10, wherein the powder X-ray diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 9.11 °, 10.94 °, 11.21 °, 12.43 °, 13.28 °, 15.34 °, 17.39 °, 18.16 °, 18.94 °, 20.18 °, 20.95 °, 22.06 °, 23.15 °, 23.35 °, 24.19 °, 25.14 °, 25.97 °, 26.75 °, 27.25 °, 28.45 °, 29.49 °, 30.16 °, 30.82 °, 33.74 °, 35.45 °, 36.39 °, 37.34 °, 38.57 °.
12. The E-type crystal described in any one of claims 8 to 11, wherein the analytical data of the XRPD pattern of the E-type crystal is as shown in the table below. 【Table 2】
13. The E-type crystal according to any one of claims 8 to 11, wherein the weight loss reaches 0.79% at 200°C ± 3°C in a thermogravimetric analysis curve.
14. The E-type crystal according to any one of claims 8 to 11, wherein a differential scanning calorimetry curve has an onset value of one endothermic peak at 250.4°C ± 2°C.
15. Use of the C-type crystal according to any one of claims 1 to 4 in the manufacture of a medicament for treating gout and hyperuricemia.
16. Use of type E crystals described in any one of claims 8 to 11 in the manufacture of a medicine for treating gout and hyperuricemia.
Citation Information
Patent Citations
Carboxylic acid substituted hetero-aromatic ring derivatives as well as preparation method and application thereof
CN106478500A
Carboxy-substituted (hetero) aromatic ring derivatives, their preparation methods, and uses
JP2018532698A
Thiophene compounds, their synthesis and medical applications
JP2019519606A
5-membered heteroaryl derivative and use thereof for medical purposes
WO2010044403A1
Thiophene derivatives as xanthine oxidase inhibitors and application thereof
WO2021083319A1
